2009
DOI: 10.1080/19320240802706866
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of an Adapted Version of the US Household Food Security Survey Module for Assessing Food Insecurity Among Low-Income Pregnant Latinas

Abstract: This study examined the internal validity of an adapted version of the U.S. Household Food Security Survey Module administered to a sample of 241 pregnant Latinas. Single-parameter logistic (Rasch) measurement model was used to assess the psychometric properties of the adapted module. Two of 14 questions examined did not fit within the acceptable range (0.70-1.30). The severity level of 12 of the 14 questions was similar across two time periods, before pregnancy and the past month of pregnancy. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The adaptations made to the US HFSSM reassured us that the revised scale had a strong potential to reliably assess household food insecurity during pregnancy among Latinas. Indeed, the quantitative validation that followed in this population indicated that the adapted US HFSSM is a valid instrument with highly desirable psychometric properties 10. Since food insecurity has been linked to many suboptimal health and nutrition outcomes among women, such as poor dietary quality, reduced food quantity, obesity, and depression, these findings have implications for helping practitioners to better understand the non-biomedical needs of the populations they serve.…”
Section: Discussionmentioning
confidence: 91%
“…The adaptations made to the US HFSSM reassured us that the revised scale had a strong potential to reliably assess household food insecurity during pregnancy among Latinas. Indeed, the quantitative validation that followed in this population indicated that the adapted US HFSSM is a valid instrument with highly desirable psychometric properties 10. Since food insecurity has been linked to many suboptimal health and nutrition outcomes among women, such as poor dietary quality, reduced food quantity, obesity, and depression, these findings have implications for helping practitioners to better understand the non-biomedical needs of the populations they serve.…”
Section: Discussionmentioning
confidence: 91%
“…For this pilot study, we used a modified FSM survey consisting of fifteen items that had been used in past studies of low-income populations to measure food insecurity (Hromi-Fiedler, Bermudez-Millan, Melgar-Quinonez, & Perez-Escamilla, 2009). Based on pilot interviews, we adapted the FSM items such that they responded to a recall period of “since being released from prison” as opposed to “in the past 12 months.” For respondents with no children, we administered the first eight FSM questions.…”
Section: Methodsmentioning
confidence: 99%
“…The survey modules in the questionnaires were either previously validated and used by other researchers [810] or by our own group among Latinos with type 2 diabetes [11]. Before starting data collection with DIALBEST participants, the survey was pre-tested among five bi-cultural/bi-lingual (Spanish and English) staff at the Hispanic Health Council, Hartford.…”
Section: Methodsmentioning
confidence: 99%
“…Socioeconomic variables included monthly income, education, employment status, and food security. Food security was assessed with a previously validated [8] short form of the US household food security supplement module [US-HFSSM] module [16]. The score ranged from 0 to 5, with five indicating extreme food insecurity (Cronbach alpha = 0.89).…”
Section: Methodsmentioning
confidence: 99%